Electrochemical characteristics of Ti-P composites prepared by mechanochemical synthesis - Woo, Sang-gil; Jung, Jin-Ho; Kim, Hansu; Kim, Min Gyu; Lee, Churl Kyung; Sohn, Hun-Joon; Choe, Byung Won (ELECTROCHEMICAL SOC INC, 2006)
Titanium phosphide composites with various Ti/P molar ratios (1:1, 1:2, and 1:4) were synthesized by a mechanochemical method and their potential use as an alternative anode material for Li secondary batteries was investigated. The titanium phosphide composites with Ti/P molar ratios of 1:1 and 1:2 did not show any electrochemical reactivity with Li, while both the TiP2 and P in the composite with a Ti/P molar ratio of 1:4 reacted with Li, yielding a reversible capacity of 1422 mAh/g. Ex situ X-ray diffraction analyses and X-ray absorption spectroscopy showed that the TiP2-P composite transformed into cubic Li10.5TiP4 phase without decomposing into Ti and Li3P during the initial Li insertion. Subsequent cycling showed a highly reversible insertion/extraction process of Li to/from Li10.5TiP4 phase, accompanied by the loss/recovery of the long-range cubic order. The cubic Li10.5TiP4 phase showed excellent cycling performance with a large capacity of 625 mAh/g for 80 cycles when the amount of lithium reacted was suitably controlled. (c) 2006 The Electrochemical Society.
Keywords: X-RAY; REACTION-MECHANISM; LITHIUM; ANODE; CU3P; LI